COVID-19 Pandemic in Democratic Republic of the Congo: An Opportunity for Economic Recovery - Modeste Ndaba Modeawi; John Likolo Baya; Bembi Bosso; Jacquie Kangu Kobe; Jonas Mbaya Kusagba; JP Mokombe Magbukudua; Masengo Ashande Colette; Gédéon Ngiala Bongo; Muhammad Ridwan; Koto-te-Nyiwa Ngbolua (Britain International of Exact Sciences (BIoEx) Journal, 2021)
The world is facing an unprecedented health crisis caused by the COVID-19 pandemic. The DR Congo with its 90 million inhabitants and more than 500,000 refugees from neighboring countries recorded the first confirmed case in Kinshasa on March 10, 2020. Currently, the country is counting 16,039 cases of infection, 566 cases of death and 13,536 cases of recovery according to the Technical Secretariat Response Team COVID-DRC, (December 23, 2020). After reporting the first case, Congolese government has taken protective health measures whereby it is in a worrying economic situation that was immediately noticeable by the increase in the rate of the foreign currency (the dollar) compared to the local currency. From an extroverted economy, the Covid-19 pandemic has put it in a situation of stagnation, which could lead country into an economic recession if this scourge persists.